Positioning Indigenous knowledge systems within the Australian mathematics curriculum: investigating transformative paradigms with Foucault. Issue 4 (4th July 2021) - Hughes, Amber
ABSTRACT: This paper is intended to provide a source of critical and theoretical reflection on the current mathematics educational objectives for Indigenous students in Australia, which are premised on acceptance of underlying concepts of 'equity'. It is not the intention of this paper to identify 'how' Indigenous knowledge can be positioned within mathematics curricula, as this would entail a philosophical inquiry much deeper than has been afforded thus far. The intent here is a consideration, facilitated through the lens of key concepts of Foucault, of some of the boundaries currently shaping the ways in which this positioning is being influenced in the mathematics, albeit neoliberal education context. Acknowledging the interplay between the social, and unconsciously shaped adoptions of what can be considered truth; knowledge; and therefore power, is a first step toward developing the openness of heart and mind needed to make real and transformative changes to education for future societies.